A Computational Study of the Effects of Tachycardia-Induced Remodeling on Calcium Wave Propagation in Rabbit Atrial Myocytes - Vagos, Márcia R.; Arevalo, Hermenegild; Heijman, Jordi; Schotten, Ulrich; Sundnes, Joakim (Frontiers in Physiology, 2021)
In atrial cardiomyocytes without a well-developed T-tubule system, calcium diffuses from the periphery towards the center creating a centripetal wave pattern. During atrial fibrillation, rapid activation of atrial myocytes induces complex remodelling in diffusion properties that result in failure of calcium to propagate in a fully regenerative manner towards the center; a phenomenon termed "calcium silencing''. This has been observed in rabbit atrial myocytes after exposure to prolonged rapid pacing. Although experimental studies have pointed to possible mechanisms underlying calcium silencing, their individual effects and relative importance remain largely unknown. In this study we used computational modelling of the rabbit atrial cardiomyocyte to query the individual effects and combined effects of the proposed mechanisms leading to calcium silencing and abnormal calcium wave propagation. We employed a population of models obtained from a newly developed model of the rabbit atrial myocyte with spatial representation of intracellular calcium handling. We selected parameters in the model that represent experimentally observed cellular remodelling which have been implicated in calcium silencing, and scaled their values in the population to match experimental observations. In particular, we changed the maximum conductances of I_CaL, I_NCX, and I_NaK, RyR open probability, RyR density, Serca2a density, and calcium buffering strength. We incorporated remodelling in a population of 16 models by independently varying parameters that reproduce experimentally observed cellular remodelling, and quantified the resulting alterations in calcium dynamics and wave propagation patterns. The results show a strong effect of I_CaL in driving calcium silencing, with I_NCX, INaK, and RyR density also resulting in calcium silencing in some models. Calcium alternans was observed in some models where I_NCX and Serca2a density had been changed. Simultaneously incorporating changes in all remodelled parameters resulted in calcium silencing in all models, indicating the predominant role of decreasing I_CaL in the population phenotype.